Utilization of Nanoparticles Produced by Aqueous-Solution Methods – Formation of Acid Sites on CeO2-TiO2 Composite and 1-D TiO2 for Dye-Sensitized Solar Cells - Adachi, Motonari; Nakagawa, Keizo; Murata, Yusuke; Kishida, Masahiro; Hiro, Masahiko; Susa, Kenzo; Adachi, Jun; Jiu, Jinting; Uchida, Fumio (IntechOpen, 2012)
None